Путешествие на край земли: [повесть] / Олег Рой - Рой Олег (Джинглики, 2015)
Экземпляры: ф.18 (20240816) / Инвентарный номер: 4986 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 65 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44